Thermal behavior of buriti biofoam - Monteiro,Sergio Neves (2010)
A natural biofoam extracted from the petiole of the buriti palm tree has shown values of density and mechanical strength with potential for uses in engineering applications such as automobile interior parts and floating components. Moreover, foams can also be used as insulating materials in packing and building panels. In this case some thermal properties are required. Therefore, the objective of this work was to evaluate the thermal behavior of the buriti biofoam by means of TGA, DTG and DSC analysis. The TGA curves revealed weight loss related to release of humidity and molecular structure decomposition. Peaks in the DTG curves indicated two intervals in temperature associated with different decomposition processes. The only endothermic DSC peak found was attributed to the lignocellulosic water of hydration being lost around 121ºC.